2007
DOI: 10.1088/0022-3727/40/23/016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Helmholtz oscillations on arc voltage fluctuations in a dc plasma spraying torch

Abstract: Arc voltage fluctuations are studied for two different plasma torches. One of them is home-made, the other is a Sultzer Metco plasma torch. Both work under similar operating conditions, but they show very different voltage waveforms and spectra, depending on their electrode configurations. The first torch shows a rather intermittent behaviour and works under the restrike mode with a rather low fluctuation amplitude and with non-reproducible spectral components. The second torch also shows characteristic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 19 publications
2
40
0
Order By: Relevance
“…Jet fluctuations induced by low frequency undulation of tri/phase rectified power supply were analyzed in [8], analysis of an effect of frequency of arc current oscillations was made in [9]. Jet instabilities caused by acoustic resonant oscillations inside the arc chamber have been described in [10,11]. Different arc voltage and chamber pressure fluctuations components, related to acoustic resonance oscillations and arc restrike oscillations, were analyzed in [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jet fluctuations induced by low frequency undulation of tri/phase rectified power supply were analyzed in [8], analysis of an effect of frequency of arc current oscillations was made in [9]. Jet instabilities caused by acoustic resonant oscillations inside the arc chamber have been described in [10,11]. Different arc voltage and chamber pressure fluctuations components, related to acoustic resonance oscillations and arc restrike oscillations, were analyzed in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of experimental studies of arc jet fluctuations were based on analysis of fluctuations of arc voltage and jet plasma radiation [12,14,21,22], sometimes frequency spectra of fluctuations of pressure inside the torch body [10,11] or exit pressure [14] were analyzed. Spatial distribution of jet fluctuations was determined from statistical analysis of jet images in [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to the assumption of Helmholtz oscillation coupling, [6] the phase difference corresponds to the propagating time of pressure perturbation caused by the voltage variation. To validate the origin of the phase difference between the arc voltage and the cathode cavity pressure, a copper tube is added between the cathode cavity and pressure sensor.…”
Section: (Received 30 June 2014)mentioning
confidence: 99%
“…Coudert and Rat [37][38][39] have studied the fluctuations of the commercial plasma torch Sulzer Metco F4 working with Ar-H 2 mixtures. For example, with a 6 mm i.d.…”
Section: Arc Stabilitymentioning
confidence: 99%
“…Attributing the mean arc spot [39] showed that the restrike mode is superimposed to the main fluctuation of arc voltage, observed around 4-5 kHz. This main oscillation is mainly due to compressibility effects of the plasma-forming gas in the rear part of the plasma torch, that is, in the cathode cavity [37,38] represented in Fig. 7.9.…”
Section: Arc Stabilitymentioning
confidence: 99%